Purity of ion beams: Analysis and simulation of mass spectra and mass interferences in ion implantation - Häublein, Volker; Ryssel, Heiner; Frey, Lothar (Advances in Materials Science and Engineering, 2012)
This paper shows that charge exchange events and dissociation reactions of ions may impact the purity of the ion beam in ion implantation, leading to contamination of the implanted target. Physical relations are derived that explain why unwanted ions are transported in the ion beam despite of a magnetic mass separation. Based on those relations, the simulation tool ENCOTION (ENergetic COntamination simulaTION) has been developed. ENCOTION is a very powerful tool for the simulation of transport mechanisms of ions through a magnet analyzer and for the simulation of mass spectra, as will be demonstrated in this paper. Copyright © 2012 Volker Hublein et al.